The Effect of Health Education about Breastfeeding Father on Husband's Knowledge at Pajangan Health Center, Bantul Yogyakarta - Susanti, Dwi; Lutfiyati, Afi (Budapest International Research and Critics University, 2021)
Mothers and husbands who have less knowledge about nutrition for pregnant women and exclusive breastfeeding are one of the causes of stunting. Prevention of stunting can be done since pregnancy and exclusive breastfeeding after the baby is born. The success of exclusive breastfeeding requires husband's support. BReastfeeding Fatheris the involvement of the father/husband in providing full support both morally and materially to his wife in the breastfeeding process. The role as a breastfeeding father requires good knowledge about breastfeeding fathers and breastfeeding. Husbands who have good knowledge have 1.7 times the possibility that the baby will get exclusive breastfeeding.This study used a quasi-experimental research method, with a one group pretest – posttest design, before giving the intervention a pretest was given, then the health education intervention was given using video, after the intervention was given a posttest. Respondents in this study were husbands of pregnant women who did Antenatal care (ANC) examinations at Pajangan Health Center Bantul Yogyakarta with a total of 30 respondents. The sampling technique used is accidental sampling. Data analysis in this study used frequency distribution and Wilcoxon's test. There is a difference in the average value of the setting before and after being given health education about breastfeeding fathers using video with a p-value of 0.000. Health education about breastfeeding fathers uses effective video media to increase husband's knowledge.